Improving the cytological diagnosis of intraocular lymphoma from vitreous fluid. Issue 1 (20th January 2015) - Ranty, Marie‐Laure; Laurent, Camille; Aziza, Jacqueline; Mahieu, Laurence; Olle, Priscille; Quintyn, Jean‐Claude; Garnier, Lorna; Bienvenu, Jacques; Collin, Laetitia; Delisle, Marie‐Bernadette; Courtade‐Saidi, Monique
<x xml:space="preserve">Abstract</x> Aims To improve the cytological diagnosis of retinal lymphoma on vitreous fluid using improved cell collection and systematic analyses. Methods and results Since October 2010, we have developed and optimized in our department a method with which to perform the diagnosis of retinal lymphoma. The vitreous sample was collected in a tube containing RPMI‐1640 medium, decomplemented fetal bovine serum, and gentamicin. The transport and technical steps were performed at 4°C. Systematically, cytological examination with May–Grünwald–Giemsa staining and immunocytochemistry (mainly anti‐CD3, anti‐CD20 and anti‐CD68 antibodies) were performed on cytospins. Whenever possible, determination of B‐cell clonality, flow cytometry and determination of the interleukin (IL)‐10/IL‐6 ratio were performed. From October 2010 to June 2013, with this optimized protocol, 38 vitreous cytological samples from 32 patients were analysed, and a final diagnosis was possible, avoiding a biopsy, in all cases except one. Conclusion The preservation of vitreous fluid cells on culture medium led to the diagnosis of retinal lymphoma in 10 of 12 cases, and exclusion of this diagnosis in 26 cases. This protocol may be applied even when the delay in shipping from the surgery to the pathology departments exceeds 1 h.